Comparison of the pathway structures influencing the temporal response of salicylate and jasmonate defence hormones in Arabidopsis thaliana - Stroud, Erin A.; Jayaraman, Jay; Templeton, Matthew D.; Rikkerink, Erik H. A. (Frontiers in Plant Science, 2022)
Defence phytohormone pathways evolved to recognize and counter multiple stressors within the environment. Salicylic acid responsive pathways regulate the defence response to biotrophic pathogens whilst responses to necrotrophic pathogens, herbivory, and wounding are regulated via jasmonic acid pathways. Despite their contrasting roles in planta, the salicylic acid and jasmonic acid defence networks share a common architecture, progressing from stages of biosynthesis, to modification, regulation, and response. The unique structure, components, and regulation of each stage of the defence networks likely contributes, in part, to the speed, establishment, and longevity of the salicylic acid and jasmonic acid signalling pathways in response to hormone treatment and various biotic stressors. Recent advancements in the understanding of the Arabidopsis thaliana salicylic acid and jasmonic acid signalling pathways are reviewed here, with a focus on how the structure of the pathways may be influencing the temporal regulation of the defence responses, and how biotic stressors and the many roles of salicylic acid and jasmonic acid in planta may have shaped the evolution of the signalling networks.